小学校特別支援学級児童の投動作の向上に関する研究 - 長曽我部, 博 (障害者スポーツ科学, 2011)
The purpose of this study was to elucidate the improvement of the overhand throwing motion for children in special needs education classes of elementary school. And to examine the feasibility of similar learning resources for them, the baton throwing method was used to learn overhand throwing motion. The subjects were 4 children with intellectual disabilities aged 8 to 11 years, and two children with autistic spectrum aged 7 and 8 years. The improvement of the overhand throwing motion was assessed via the "achievement score" for the throwing motion evaluation standard, and by analyzing the throwing motion with VTR and measuring the throw distance. Before the first non-treatment period, four children had improved but two children didn't have improved, their average "achievement score" from 18.2 points to 20.3 points. Four children increased but two children decreased, their average throwing distance from 476.8cm to 537.2cm. After the first non-treatment period, the following teaching adaptations for overhand throwing were made based on each individual's needs. 1. Setting a target and using a sound effect to increase the swing speed of the arm. 2. Offering advice to achieve a rhythmic and smooth overhand throwing motion. 3. Preparing a mark which indicates the release point when throwing a ball. After these adapted sessions, all children had improved their average "achievement score" from 20.3 points to 28.0 points. All children increased their average throwing distance from 537.2cm to 640.8cm.